`Can you pass the salt?' The legitimacy of international institutions and indirect speech - Matthew D. Stephen (European Journal of International Relations, 2015)
This article introduces the concept of indirect speech and shows what it can contribute to understanding `legitimacy talk' regarding international institutions. Indirect speech occurs when one kind of illocutionary act is used to communicate another. Examples include euphemism, some forms of politeness and when a request is expressed as a question (`Can you pass the salt?'). Transporting concepts from pragmatics and sociolinguistics, this article argues that legitimacy talk often serves this function in international politics, operating by expressing specific requests in the form of more generalized legitimacy claims. Understanding this double role of legitimacy talk sheds light on otherwise puzzling empirical phenomena, such as why states frame their demands in terms of legitimacy when they are transparently self-serving, why states with different interests can nonetheless express their demands in the same terms, and why they persist in doing so long after there is any realistic hope of being `persuasive'. An analysis of the debate on Security Council reform illustrates the benefits of this approach for the study of international relations.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; dialogue; diplomacy; institutions; legitimacy; rhetoric; Security Council